2005
DOI: 10.1111/j.1469-0691.2004.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term surveillance of invasive group A streptococcal disease in The Netherlands, 1994–2003

Abstract: A nationwide laboratory-based surveillance study of invasive group A streptococcal (GAS) infections was conducted in The Netherlands from May 1994 until December 2003 (average population during this period was 15 729 704). Microbiologically invasive isolates were obtained from 1504 patients, with most (70%) isolates cultured from blood. There was a clear seasonal pattern in invasive streptococcal infections, with an estimated annual incidence that peaked in 1996 (4.0 cases/100 000 individuals/year) and was at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 42 publications
5
25
0
3
Order By: Relevance
“…In the present study, speA was also detected in all isolates of the two major PFGE clusters, but all other isolates lacked speA, and the most frequent exotoxin gene found was speC. The exotoxin gene profile of the main invasive clone in Portugal is in agreement with previous reports for isolates of the same emm type (emm1) in other countries (2,18,23). On the other hand, though ssa has recently been reported as being more prevalent among M1/emm1 invasive isolates than among M1/emm1 noninvasive isolates (4, 17), it was not found among any of the emm1 isolates in this study.…”
supporting
confidence: 81%
“…In the present study, speA was also detected in all isolates of the two major PFGE clusters, but all other isolates lacked speA, and the most frequent exotoxin gene found was speC. The exotoxin gene profile of the main invasive clone in Portugal is in agreement with previous reports for isolates of the same emm type (emm1) in other countries (2,18,23). On the other hand, though ssa has recently been reported as being more prevalent among M1/emm1 invasive isolates than among M1/emm1 noninvasive isolates (4, 17), it was not found among any of the emm1 isolates in this study.…”
supporting
confidence: 81%
“…With the reemergence of invasive GAS disease in the 1980s, there have been numerous reports published describing the burden of GAS disease in industrialized countries (7,9,13,(17)(18)(19)(20)36). In these reports, invasive GAS disease rates ranged from 1.5 to 5.8 cases/100,000 persons.…”
Section: Discussionmentioning
confidence: 99%
“…The mean incidence during the study period was 2.6 cases per 100,000 inhabitants, which was similar to that during the last two decades in Denmark (16) and to other reported Scandinavian data (10,16,19,54). Population-based surveillance studies from the United States, Canada, and The Netherlands have shown rates ranging between 1.5 and 5 cases per 100,000 inhabitants per year (30,36,37,56). A seasonal fluctuation could be observed, with an elevated number of cases during January to April, which could be explained by the well-known influence of indoor overcrowding on transmission of streptococci (46).…”
Section: Discussionmentioning
confidence: 99%